Chitosan and Anionic Solubility Enhancer Sulfobutylether-β-Cyclodextrin-Based Nanoparticles as Dexamethasone Ophthalmic Delivery System for Anti-Inflammatory Therapy - Giuseppe Francesco Racaniello; Gennaro Balenzano; Ilaria Arduino; Rosa Maria Iacobazzi; Antonio Lopalco; Angela Assunta Lopedota; Hakon Hrafn Sigurdsson; Nunzio Denora (MDPI AG, 2024)
Cataract surgery interventions are constantly increasing, particularly among adult and elderly patients. This type of surgery can lead to inflammatory states of the ocular anterior segment (AS), usually healed via postoperative treatment with dexamethasone (DEX)-containing eye drops. The application of eye drops is challenging due to the high number of daily administrations. In this study, mucoadhesive nanoparticles (NPs) were formulated to improve the residence time of DEX on the corneal mucosa, enhancing the drug's solubility and bioavailability. The NPs were generated using an ionotropic gelation technique, exploiting the interaction between the cationic group of chitosan (CS) and the anionic group of sulfobutylether-β-cyclodextrin (SBE-β-CD). The formation of the inclusion complex and its stoichiometry were studied through phase solubility studies, Job's plot method, and Bi-directional transport studies on MDCKII-MDR1. The obtained NPs showed good chemical and physical characteristics suitable for drug loading and subsequent testing on animal mucosa. The DEX-loaded CS/SBE-β-CD NPs exhibited a prolonged residence time on animal mucosa and demonstrated enhanced drug permeability through the corneal membrane, showing a sustained release profile. The developed NPs posed no irritation or toxicity concerns upon local administration, making them an optimal and innovative drug delivery system for inflammatory AS diseases treatment.